2012
DOI: 10.1007/s00122-012-1985-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of combining ability loci for five yield-related traits in maize using a set of testcrosses with introgression lines

Abstract: Combining ability is essential for hybrid breeding in crops. However, the genetic basis of combining ability remains unclear and has been seldom investigated. Identifying molecular markers associated with this complex trait would help to understand its genetic basis and provide useful information for hybrid breeding in maize. In this study, we identified genetic loci of general combining ability (GCA) and specific combining ability (SCA) for five yield-related traits under three environments using a set of tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 23 publications
4
45
0
Order By: Relevance
“…In the current study, we used a SSL to investigate PM resistance in cucumber. SSL508-28 possessed a segment from the PM resistant donor (Jin5-508), allowing for more precise detection of the PM responsive genes [34]. In PM inoculation tests conducted over 3 years, the resistance of SSL508-28 was found to be highly consistent and stable, suggesting that the introgressed fragment truly carried a PM resistant locus.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we used a SSL to investigate PM resistance in cucumber. SSL508-28 possessed a segment from the PM resistant donor (Jin5-508), allowing for more precise detection of the PM responsive genes [34]. In PM inoculation tests conducted over 3 years, the resistance of SSL508-28 was found to be highly consistent and stable, suggesting that the introgressed fragment truly carried a PM resistant locus.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, the analysis of G × E revealed that there were no evident differences among the three environments. For most experiments which are about yield performance, the effect of environments is always significant because the sites are set at very different environment which are far away from each other to study the effect of environment on the yield (Xiang et al, 2001;Shi et al, 2009;Qi et al, 2013). In this case, the first thing to be considered about when designing the experiment is the effect of waterlogging on the yield.…”
Section: The Environment Effectmentioning
confidence: 99%
“…It has being successfully applied in crop and livestock breeding for the evaluation of parent performance [3-5]. However, in spite of this, the genetic analysis of the GCA is very limited [6,7], and the molecular mechanism of the GCA has not been documented. In the present study, we found that certain phenotypes in rice F1 hybrids were always biased toward the positive GCA effect parents in the traits tested (r > 0.97, P <  3.80E-07).…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al found that several genetic loci responding for GCA and SCA for five yield-related traits using a set of testcrosses with introgression lines (ILs) of maize under different environmental conditions. Total of 56 significant QTL GCA loci have been mapped [7]. These studies have revealed that GCA effects, like the traits, are genetically controlled.…”
Section: Introductionmentioning
confidence: 99%